KESADARAN HUKUM MASYARAKAT DALAM PENGGUNAAN PUPUK BERSUBSIDI DILUAR PERUNTUKANNYA BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 1992 TENTANG SISTEM BUDIDAYA TANAMAN DI WILAYAH HUKUM DESA SUNGAI JANIAH KECAMATAN BASO KABUPATEN AGAM PROVINSI SUMATERA BARAT - Akmal Astani; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Society is the source of social contact with humans in general. In the case of FertilizerBersubsisdi society must have the knowledge of the Subsidized Fertilizer, which will give theLegal Awareness for communities and can guide you in everyday life.This research is a sociological research that want to see the unity between law and societywith the gap between fennel and das sein sollen. This research was conducted in thejurisdiction of Sungai Janiah District of Baso Agam West Sumatra province, while the samplepopulation is a whole party related to the issues examined in this study, the data source used,primary data, secondary data and data tertiary, technical data collection in this research wasconducted through interviews and review of the literature.From the results of research can be concluded, first, the level of legal awareness in SungaiJaniah Baso Subdistrict Provision Agam West Sumatra is still low. Second, the barriers facedby internal factors are the obstacles include the lack of attention of government factors interms miningkatkan legal awareness in society and the lack of seriousness of the governmentin terms of increasing awareness of the law. While his external factors include the lack ofeducational background masyarat and indifferent attitude of society to the law so that interms of increasing awareness of the law is an obstacle and makes the authority of the law inthe eyes of society so becoming weaker. Third, efforts to overcome the barriers that fix theinternal shortcomings by providing counseling-penyulahan to the public on legal awarenessby understanding easily understood by all circles of society and this can be done duringcampaigns or events organized by the government. And instill a sense of awareness of the lawto the public early review will be accompanied by awareness of the law itself.Keywords : Legal Awareness - Subsidized Fertilizer - Level of Legal Awareness